The Effectiveness of Mentoring Access to LAZ Ulil Albab Education Scholarships in Medan City - Hasan Sazali; Mailin Mailin; Khairatun Hisan (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Poverty is one of the complex problems in society. The factor is the low level of public education, giving rise to various social problems, such as unemployment and dropping out of school, such as unemployment and dropping out of school. This study aims to determine the effectiveness of the mentoring program in fostering and empowering LAZ Ulil Albab educational scholarship recipients aim to raise the dignity of the underprivileged to be more independent. This type of research is qualitative in a descriptive approach and is field research. Data collection techniques used interviews, observation, and documentation. Data analysis uses data reduction, data presentation, and verification. The theory used in this study uses social exchange theory and compliance theory. The results obtained, the stages in changing the behavior, mindset, and educating the independence of scholarship participants are very effectively carried out by communicators with intensive coaching methods, namely the provision of intensive Islamic material, life skills training, and empowerment of LAZ Ulil Albab scholarship participants in social activities.